The Sociodemographic Factors Associated With Multimorbidity In Patients With Diabetes Mellitus Type 2 In District Hospital Sukoharjo Central Java. - Oktaviano Rahayuningrum, Indriyati; Maryati, Warsi; Cahya Faiza, Meilia (LPPM Universitas Duta Bangsa Surakarta, 2024)
Background: Multiple chronic diseases known as multimorbidity are one of the global public health challenges. Multimorbidity among older adults was more than 50% in different countries. This study aimed to analyze the sociodemographic factors associated with multimorbidity in patients with diabetes mellitus type 2 in District Hospital Sukoharjo Central Java. Methods: This study used a cross-sectional approach utilizing medical record data of diabetes mellitus patients. Consecutive sampling was conducted, and 75 samples were included. A descriptive analysis was performed by reporting percentages. Bivariate analysis was conducted using Chi-square. Logistic regression with a 5% significance level was used to analyze the multivariable. Results: The prevalence of multimorbidity was 33 (44%). The sociodemographic factors associated with multimorbidity were age (p=0.039), gender (p=0.032), education (p=0.028), status of employment (p=0.020), and length of stay (p=0.011). Logistic regression showed an association between length of stay (OR=3.93;95%CI=1.29-11,92; p=0.016) and multimorbidity. Conclusion: Based on these findings, the sociodemographic factors associated with multimorbidity in patients with diabetes mellitus type 2 were: age, gender, education, status of employment, and length of stay. The programs to prevent multimorbidity should be formulated. Early detection and health promotion can be managed to decrease multimorbidity in patients with diabetes mellitus type 2.